Proceedings of Third Doctoral Symposium on Computational Intelligence DoSCI 2022 - Khanna, Ashish; Gupta, Deepak; Kansal, Vineet; Fortino, Giancarlo; Hassanien, Aboul Ella (Lecture Notes in Networks and Systems, 2023)
XXXIV, 861 p. 430 illus., 328 illus. in color.